Employment and Industrialization in Developing Countries: Comment - Ross, David F. (Quarterly Journal of Economics, 1967)
Journal Article Employment and Industrialization in Developing Countries: Comment Get access David F. Ross David F. Ross Cuttington College, Liberia, West Africa Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 81, Issue 2, May 1967, Pages 338–342, https://doi.org/10.2307/1879592 Published: 01 May 1967